El enmarcado de la mente: análisis de una clave central de la visión del poder de Manuel Castells - Torres, Esteban (2013)
In this paper, we analize in systematic and detailed terms one central aspect of Manuel Castells´s contemporary sociological perspective of power: the question of frame or modeling mind. The research will allow us to discover, mainly, the proliferation of a discourse built from two theoretical operations hidden by the author: the postulation of a logic of imposition as exclusionary logic of power or power of framed, and the separation between power and minds. We demonstrate that such discourse embodies a contradictory movement as often assumed a markedly ideological form that tend to mask the mentioned operations. Castells´s appropriation of Entman´s theory, his mainly theoretical source inthis case, provides significant evidence to demonstrate such findings.